2014
DOI: 10.1039/c3ra47769j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of antiferromagnetic Co3O4 nanoparticles from two different precursors by pyrolytic method: in vitro antimicrobial activity

Abstract: Two varieties of Co3O4 nano particles (Co3O4-I and Co3O4-II) have been synthesized from two different precursors using a pyrolytic technique and their magnetic and in vitro antimicrobial activity have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The shape of a nanomaterial affects cellular uptake, biocompatibility, and retention in tissues and organs (George et al, 2014;Pal, Tak, & Song, 2007). It was also reported that modulation of the shape of NPs can alter their flow in the systemic circulation, adhesion properties with cells, and circulation time (Doshi et al, 2014;Geng et al, 2009).…”
Section: Technical Challengesmentioning
confidence: 99%
“…The shape of a nanomaterial affects cellular uptake, biocompatibility, and retention in tissues and organs (George et al, 2014;Pal, Tak, & Song, 2007). It was also reported that modulation of the shape of NPs can alter their flow in the systemic circulation, adhesion properties with cells, and circulation time (Doshi et al, 2014;Geng et al, 2009).…”
Section: Technical Challengesmentioning
confidence: 99%
“…These ROS disintegrate all the structural building blocks of bacterial cells, i.e., carbohydrates, proteins and lipids by interacting with them which eventually cause death of bacteria. They also interact with the genetic material of bacteria and interrupt DNA replication, transcription and protein synthesis which lead to bacterial death (Wang et al 2010;Dasari et al 2013;Ghosh et al 2014;Khan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The catalytic activity of Co3O4 strongly depends on structural parameters including its surface area, size and morphology. 3,6 A range of synthesis methods including electrodeposition, 7 spray pyrolysis, 8 chemical vapor deposition, 9 atomic layer deposition, 10 and transformation of precursors such as Co (II) salts [11][12][13][14] and coordination compounds 15 have therefore been explored to generate cobalt oxide nanostructures. With their tendency towards the formation of low-dimensional, anisotropic structures with high surface areas, 16,17 and the production of non-toxic gaseous products during their thermal conversion into Co3O4, the precursor-led methods based on the decomposition of cobalt hydroxides, carbonates and basic carbonates are particularly attractive.…”
Section: Introductionmentioning
confidence: 99%